2022
DOI: 10.3389/fmolb.2022.887758
|View full text |Cite
|
Sign up to set email alerts
|

RecQ Helicase Somatic Alterations in Cancer

Abstract: Named the “caretakers” of the genome, RecQ helicases function in several pathways to maintain genomic stability and repair DNA. This highly conserved family of enzymes consist of five different proteins in humans: RECQL1, BLM, WRN, RECQL4, and RECQL5. Biallelic germline mutations in BLM, WRN, and RECQL4 have been linked to rare cancer-predisposing syndromes. Emerging research has also implicated somatic alterations in RecQ helicases in a variety of cancers, including hematological malignancies, breast cancer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 240 publications
0
5
0
Order By: Relevance
“…BLM, an important member of the RecQ family of helicases, is associated with an increase in cancer predisposition (Thakkar et al 2022). It is known for its functions in DNA replication, repair and telomere maintenance (Rezazadeh 2013).…”
Section: Introductionmentioning
confidence: 99%
“…BLM, an important member of the RecQ family of helicases, is associated with an increase in cancer predisposition (Thakkar et al 2022). It is known for its functions in DNA replication, repair and telomere maintenance (Rezazadeh 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The RecQ family of helicases represents one of the most highly conserved groups of 3′-5′ DNA helicases and is named after the prototype Escherichia coli RecQ, called RECQL1, BLM, WRN, RECQL4, and RECQL5. Biallelic mutations in these RecQ homologs, WRN, BLM, and RECQL4, have been previously reported to be associated with rare human genetic diseases characterized by chromosomal instability and cancer susceptibility ( Croteau et al, 2014 ; Thakkar et al, 2022 ). In 2022, Abu-Libdeh et al reported that RECQL1 mutations can induce impaired DNA damage repair ability and lead to RECON syndrome, a genome instability disorder ( Abu-Libdeh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…RECQL5 deficiency may disrupt RAD51 recombinase nucleoprotein filaments and lead to genome instability ( Hu et al, 2007 ; Andrs et al, 2020 ). Several studies have also indicated that RECQL5 was involved in multiple hereditary cancer susceptibility ( Tavera-Tapia et al, 2019 ; Xia et al, 2021 ; Thakkar et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Significant variations in mRNA and protein levels were observed among different types of cancer in RECQs. Earlier findings suggested that the RECQs expression showed notable differences between tumors and non-neoplastic conditions [ 38 ]. In tumors, somatic chromosomal deletions and replications are characterized by CNVs, indicating that it may serve as a fertile environment for acquired alterations in cancer cells [ 39 ].…”
Section: Discussionmentioning
confidence: 99%